2021
DOI: 10.3389/fendo.2021.619568
|View full text |Cite
|
Sign up to set email alerts
|

Within-Person Variation in Serum Thyrotropin Concentrations: Main Sources, Potential Underlying Biological Mechanisms, and Clinical Implications

Abstract: BackgroundIndividuals exhibit fluctuations in the concentration of serum thyroid-stimulating hormone (TSH) over time. The scale of these variations ranges from minutes to hours, and from months to years. The main factors contributing to the observed within-person fluctuations in serum TSH comprise pulsatile secretion, circadian rhythm, seasonality, and ageing. In clinical practice and clinical research however, such within-person biological variation in serum TSH concentrations is often not considered. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 126 publications
1
23
1
Order By: Relevance
“…The present study found little effects of altitude on serum TSH among Tibetans, which is consistent with the results of an observation study (11). Relatively short half-life of TSH (17 to 93 min) (15), pulsatile secretion manners (15,22) and feedback regulation of the HPT axis may roughly explain the phenomenon, although the exact mechanism is unclear. In euthyroid people, synthetic TSH is released in a manner combining a basal (non-pulsatile) and a pulsatile form and can be promptly cleared after action on the thyroid gland.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found little effects of altitude on serum TSH among Tibetans, which is consistent with the results of an observation study (11). Relatively short half-life of TSH (17 to 93 min) (15), pulsatile secretion manners (15,22) and feedback regulation of the HPT axis may roughly explain the phenomenon, although the exact mechanism is unclear. In euthyroid people, synthetic TSH is released in a manner combining a basal (non-pulsatile) and a pulsatile form and can be promptly cleared after action on the thyroid gland.…”
Section: Discussionsupporting
confidence: 92%
“…This long-term adaptation may lead to thyroid-related hormone levels in Tibetans different from those in the plain (9)(10)(11). Even if the effects of sex, age (12)(13)(14), region, sampling time (15), and pregnancy status (16) on thyroid-related hormones are well discussed, however, only few articles (10,11,17) have assessed the influence of altitude on thyroid-associated hormones, let alone establishing altitudespecific RIs.…”
Section: Introductionmentioning
confidence: 99%
“…2) [1]. Though there are many potential sources of intraindividual variation in thyroid function [14], FT4 and TSH levels tend to be relatively stable for each healthy individual in the population such that inter-individual variation, as manifest as the population range, is greater than intra-individual variation [15]. This stability in turns implies intra-individual stability of thyroid and pituitary sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol is a catabolic (Brillon et al 1995, Simmons et al 1984 and stress-related hormone (Russell and Lightman 2019) that inhibits testosterone secretion (Cumming et al 1983); thus, changes in cortisol concentration alter the body anabolic-catabolic balance. Also, cortisol presents an inhibitory effect on TSH secretion (Van der Spoel et al 2021, Re et al 1976). The stress of moderate and intense physical exertion is an additional stimulus for cortisol secretion (Hill et al 2008).…”
Section: Introductionmentioning
confidence: 99%